Հայոց նոր և նորագույն պատմության կարևոր մի աղբյուր - Մուրադյան, Սամվել («Զանգակ - 97»)
Continuing our previous publication we are producing a new part of the Memories of Hajk Astvatsatryan. It eoncerns to the political, economic and militaiy events which took place from March 7 to March 22, in 1918, in Transcaucasus. Its worth to pay a special attention to the politics of Turkey deal to the new formed administrative unions of Caucasus, scparatcd from Russia. It refers to the new anti-Annenian exposures of Azerbaijan, also to the position adopted by Georgia to the Armenian-Turkish relations.
Keywords: Պատմություն